2008
DOI: 10.1128/aac.01130-07
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Zidovudine (AZT) and Its Intracellular Phosphate Metabolites in AZT- and AZT-Lamivudine-Treated Newborns of Human Immunodeficiency Virus-Infected Mothers

Abstract: Newborns from human immunodeficiency virus-infected mothers are given antiretroviral prophylaxis against mother-to-child transmission, including predominantly nucleoside reverse transcriptase inhibitors. Pharmacological monitoring of these drugs in newborns has so far been limited to plasma and cord blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Indeed, high levels of AZT/AZT monophosphate (AZ-MP)/AZT-TP, and 3TC-TP were consistent with short-term hematological disturbance observed in clinics (7,11). If, as suggested by the literature (10), this overexposure was related to a more efficient phosphorylation due to a higher activation in the peripheral blood mononuclear cells (PBMCs) of the neonates than in adults, it could be the same for TFV-DP and could cause toxicity problems. It is important with this background to verify that neonatal intracellular TFV-DP concentrations in PBMCs are not too high following PMTCT exposure.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Indeed, high levels of AZT/AZT monophosphate (AZ-MP)/AZT-TP, and 3TC-TP were consistent with short-term hematological disturbance observed in clinics (7,11). If, as suggested by the literature (10), this overexposure was related to a more efficient phosphorylation due to a higher activation in the peripheral blood mononuclear cells (PBMCs) of the neonates than in adults, it could be the same for TFV-DP and could cause toxicity problems. It is important with this background to verify that neonatal intracellular TFV-DP concentrations in PBMCs are not too high following PMTCT exposure.…”
mentioning
confidence: 51%
“…Newborns are likely to be overexposed to intracellular phosphorylated nucleoside reverse transcriptase inhibitors (NRTIs), as was shown for lamivudine triphosphate (3TC-TP) and zidovudine triphosphate (AZT-TP) during the first 2 weeks of life (10). Indeed, high levels of AZT/AZT monophosphate (AZ-MP)/AZT-TP, and 3TC-TP were consistent with short-term hematological disturbance observed in clinics (7,11).…”
mentioning
confidence: 74%
“…69 Another study also found higher ZDV phosphates (MP plus DP plus TP) among 5 women versus 16 men (1.4-fold; P < 0.01), and a third study found higher 3TC-TP in female compared with male infants despite similar plasma concentrations (1.8-fold; P = 0.04). 61,81 However, a separate study found lower ZDV-triphosphates in female compared with male adults although plasma concentrations were similar. 82 An in vitro study evaluated the effects of progesterone, estrogen, and testosterone on conversion of ZDV and 3TC to ZDV-TP and 3TC-TP in PBMCs and found no major effects, but some minor lowering on 3TC-TP for progesterone and testosterone (all differences were below 50% versus control).…”
Section: Clinical Pharmacokineticsmentioning
confidence: 98%
“…61,[69][70][71] The half-life of ZDV-TP is about 7 hours and that for 3TC-TP is about 22 hours. 69 These half-lives for the pharmacologically active moieties are several-fold longer than the parent drug in plasma, and form the pharmacokinetic rationale for the dosing frequencies used in patients today (twice daily for ZDV and once-or twice-daily for 3TC).…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation